"Sick but active, tired but healthy". Narratives of body and self living with HIV. Issue 4 (4th July 2022) - Schuft, Laura; Ferez, Sylvain; Bergamaschi, Alessandro; d'Arripe-Longueville, Fabienne
ABSTRACT: Although studies have suggested that physical activity may diminish HIV-related fatigue, little is known about the physical experience or meanings attributed to either. We considered chronic fatigue and physical activity in terms of how they were experienced, interpreted and interrelated within narratives about living with HIV. Thematic analysis of 35 semi-structured interviews with people living with HIV in France led to the creation of four ideal-type narratives. The ideal types illustrated relations between diverse physical and social experiences of fatigue and physical activity. These dimensions of the HIV experience were part of larger identity narratives about the body and self, revealing tensions between the latter as healthy or ill, tired or active, vulnerable or robust, needing or heeding expected health behaviours. Illness narratives – and the meanings attributed to body and self – emerged as faceted by both physical experiences of the body and social experiences, and as situated within larger socio-political contexts and biopedagogies.